NBS-Encoding Genes in Brassica napus Evolved Rapidly After Allopolyploidization and Co-localize With Known Disease Resistance Loci - Fu, Ying; Zhang, Yaofeng; Mason, Annaliese S.; Lin, Baogang; Zhang, Dongqing; Yu, Huasheng; Fu, Donghui (Frontiers in Plant Science, 2019)
Genes containing nucleotide-binding sites (NBS) play an important role in pathogen resistance in plants. However, the evolutionary fate of NBS-encoding genes after formation of allotetraploid Brassica napus is still unknown. We performed a genome-wide comparison of putatively functional NBS-encoding genes in B. napus and its progenitor species Brassica rapa and Brassica oleracea, identifying 464, 202 and 146 putatively functional NBS-encoding genes respectively, with genes unevenly distributed in several clusters. The An-subgenome of B. napus possessed similar numbers of NBS-encoding genes (191 genes) to the Ar genome of B. rapa (202 genes) and similar clustering patterns. However, the Cn genome of B. napus had many more genes (273) than the B. oleracea Co genome (146), with different clustering trends. Only 97 NBS-encoding genes (66.4%) in B. oleracea were homologous with NBS-encoding genes in B. napus, while 176 NBS-encoding genes (87.1%) were homologous between B. rapa and B. napus. These results suggest a greater diversification of NBS-encoding genes in the C genome may have occurred after formation of B. napus. Although most NBS-encoding genes in B. napus appeared to derive from the progenitors, the birth and death of several NBS-encoding genes was also putatively mediated by non-homologous recombination. The Ka/Ks values of most homologous pairs between B. napus and the progenitor species were less than 1, suggesting purifying selection during B. napus evolution. The majority of NBS-encoding genes (60% in all species) showed higher expression levels in root tissue (out of root, leaf, stem, seed and flower tissue types). Comparative analysis of NBS-encoding genes with mapped resistance QTL against three major diseases of B. napus (blackleg, clubroot and Sclerotinia stem rot) found 204 NBS-encoding genes in B. napus located within 71 resistance QTL intervals. The majority of NBS-encoding genes were co-located with resistance QTLs against a single disease, while 47 genes were co-located with QTLs against two diseases and 3 genes were co-located with QTLs against all three. Our results revealed significant variation as well as interesting evolutionary trajectories of NBS-encoding genes in the different Brassica subgenomes, while co-localization of NBS-encoding genes and resistance QTL may facilitate resistance breeding in oilseed rape.